Data Governance in Lakehouse - Shah, Samarth; Jain, Shubham (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Data governance in a lakehouse architecture is crucial for managing the lifecycle, quality, and security of data across hybrid and scalable environments. The lakehouse model combines the benefits of data lakes and data warehouses, enabling organizations to handle large volumes of structured and unstructured data while ensuring analytical accuracy. However, the seamless integration of diverse data sources introduces challenges related to governance, including compliance, privacy, and data lineage. This paper explores the principles and practices essential for implementing effective data governance in a lakehouse environment. Key components such as metadata management, data cataloging, access control, and policy enforcement are discussed in detail. The role of automation and machine learning in enhancing governance capabilities, such as detecting anomalies and ensuring compliance with regulatory standards, is also examined. Additionally, the lakehouse architecture's unified nature demands a governance framework that ensures data consistency while fostering accessibility for both data scientists and business analysts. Strategies for integrating data governance within the lakehouse model, including role-based access, audit trails, and encryption, are presented to mitigate risks and enhance trust in data usage. By addressing these challenges and opportunities, this paper demonstrates how a robust data governance framework can empower organizations to balance innovation and control. Ultimately, data governance in the lakehouse architecture serves as a foundation for reliable, secure, and actionable insights, driving informed decision-making in complex and dynamic environments.